The Impact and Integration of Fintech on Traditional Financial Institutions - Wang, Ziwei (International Journal of Global Economics and Management, 2024)
With the rise of financial technology, traditional financial institutions are facing unprecedented impact and opportunities. This paper provides an in-depth analysis of the impact of fintech on traditional financial institutions and the integration and development of the two. Firstly, the research background and purpose of the integration of fintech and traditional financial institutions are described. Then it analyses the development status of fintech and traditional financial institutions, including the development history and characteristics of fintech and the status quo and challenges of traditional financial institutions. Then it discusses the impact of fintech on traditional financial institutions at the business level and profit model. After that, the integration mode of fintech and traditional financial institutions is elaborated, including technology application integration and cooperation case study. Then it looks forward to the future trend of the integration of FinTech and traditional financial institutions, including the development direction outlook and the future pattern and competitive situation. Finally, the research conclusions are summarised and the future research direction is outlooked. The integration of fintech and traditional financial institutions is an unstoppable trend, and traditional financial institutions should actively respond to the challenges and seize the opportunities to achieve higher quality development.